Comparing the Effectiveness of a Parenting Package Based on Responsiveness to Mothers' Parenting Needs with Organizational Skills Training on Academic Emotion, Task Avoidance Behavior, and Organizational Skills in Children Aged 8-12 with sluggish Cognitive Te - Arjhang, Nasim; Bahramipourisfahani, Mansoureh; Yousefi , Zahra (Health Nexus, 2023)
This study aimed to compare the effectiveness of a parenting package based on responsiveness to mothers' parenting needs with organizational skills training on academic emotion, task avoidance behavior, and organizational skills in children aged 8-12 with sluggish cognitive tempo. The statistical population included all mothers of children aged 8-12 with slow cognitive tempo during the 2023-2024 academic year in the city of Isfahan. A sample size of 45 mothers of children with slow cognitive tempo was selected based on the Slow Cognitive Tempo Questionnaire - Parent Form and entry criteria through purposive sampling and randomly assigned to two experimental groups and one control group (each group consisting of 15 members). The experimental groups received training on the parenting package based on mothers' needs and organizational skills training, each comprising 12 sessions of 60 minutes, while the control group received no training. After the training sessions concluded, post-tests were administered to all groups. Data collection was conducted using tools such as the Slow Cognitive Tempo Questionnaire - Parent Form, the Child Organization Skills Scale - Parent Form, the Pekrun et al. (2011) Academic Emotion Questionnaire, and the Conners' Parent Rating Scale (1998). Data were analyzed using descriptive statistics, including mean and standard deviation, and inferential analysis using repeated measures ANOVA. The results indicated that the parenting package based on mothers' needs had a significantly greater effect on academic emotion, task avoidance behavior, and organizational skills compared to organizational skills training, and both interventions had a significant impact compared to the control group (p < 0.01). According to the results, training based on responsiveness to mothers' needs can help mothers understand their children's needs and issues, consequently addressing their problems, including task avoidance behavior and negative academic emotions, and improving their organizational skills.